2018
DOI: 10.1002/pds.4647
|View full text |Cite
|
Sign up to set email alerts
|

Adherence trajectories of buprenorphine therapy among pregnant women in a large state Medicaid program in the United States

Abstract: Six buprenorphine treatment trajectories during pregnancy were identified in this population-based Medicaid cohort, with 25% of women initiating buprenorphine late during pregnancy. Understanding trajectories of buprenorphine use and factors associated with discontinuation/nonadherence may guide integration of behavioral treatment with obstetrical/gynecological care to improve buprenorphine treatment during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 39 publications
(96 reference statements)
1
35
0
Order By: Relevance
“…Our chosen medication use criteria were intended to limit this by only including individuals receiving a buprenorphine product indicated for OUD. (14,16,17) Although we excluded individuals changed residential ZIP code at any point while receiving buprenorphine, some individuals may have moved into the state in the six-months prior to initiating treatment leading to misclassification as incident users. Leaving the state would not be expected to impact exposure or outcome measurement as gaps and changes in pharmacy were recorded in the record after they had occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our chosen medication use criteria were intended to limit this by only including individuals receiving a buprenorphine product indicated for OUD. (14,16,17) Although we excluded individuals changed residential ZIP code at any point while receiving buprenorphine, some individuals may have moved into the state in the six-months prior to initiating treatment leading to misclassification as incident users. Leaving the state would not be expected to impact exposure or outcome measurement as gaps and changes in pharmacy were recorded in the record after they had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The entire study duration was January 1, 2016-December 31, 2018. Index use of buprenorphine was defined by the initial prescription of a buprenorphine product indicated for opioid use disorder (14,16,17) during the identification period between June 30, 2016 and July 1, 2018. To ensure that only incident buprenorphine patients were included, we excluded individuals who used any buprenorphine product between January 1 and July 1, 2018.…”
Section: Study Design and Samplementioning
confidence: 99%
“…Studies have also described racial and ethnic disparities in the treatment of OUD 6,7 . Recent research is documenting a similar trend among pregnant women, with women of color being less likely to receive medication to manage OUD and more likely to experience inconsistent use or discontinuation 8,9 …”
Section: Racial and Ethnic Disparities In The Treatment Of Opioid Usementioning
confidence: 99%
“…8 More recently, a retrospective cohort study of pregnant Medicaid recipients receiving buprenorphine demonstrated late initiation and discontinuation of medication during pregnancy is associated with the following factors: younger age, non-white race, residents of rural counties, fewer outpatient visits, more frequent emergency department visits, and hospitalizations, and lower buprenorphine daily dose. 9 The "fourth trimester" or first 12 weeks postpartum corresponds to a time of increased maternal stress due to the associated caretaking responsibilities of a newborn child. This stress and other associated stressors, such as time and financial constraints, are possible reasons for treatment discontinuation during the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently published a study that identified risk factors for treatment adherence during pregnancy until delivery and found that higher clinically rated withdrawal symptoms at last visit attended and lower daily buprenorphine doses were associated with nonadherence 8 . More recently, a retrospective cohort study of pregnant Medicaid recipients receiving buprenorphine demonstrated late initiation and discontinuation of medication during pregnancy is associated with the following factors: younger age, non‐white race, residents of rural counties, fewer outpatient visits, more frequent emergency department visits, and hospitalizations, and lower buprenorphine daily dose 9 …”
Section: Introductionmentioning
confidence: 99%